(untitled) (European Journal of Education and Psychology, 2010)
We present a research about the effects of the application of a program of improvement of the creativity in a classroom of Primary School. The used total sample was of 90 students, pertaining to a preschool and Primary School, of the region of the Altiplano (municipality of Jumilla) in the Region of Murcia (Spain). With this study we want to demonstrate that the implementation of a program that develops the divergent thought, is going to influence favorably in the creativity of the students. The results indicate a significant improvement in the fluidity factors, flexibility and originality, in the groups to which it was applied to the program of improvement of the creativity of Renzulli, specially in the students of the first cycle of Primary Education. What the investigation confirms is that a program of development of the creativity, represents an instrument for teachers and children who provide tasks and materials with which to try a variety of ways to express its creative potential.